Developing a Scalable IoT Security Compliance Framework for Strengthening the Security Posture of FinTech MSMEs: A Quantitative Approach - Pillai, Arun Sasidharan (Digital Repository of Theses - SSBM Geneva, 2025)
This research investigates the security challenges posed by Internet of Things (IoT) technologies within Fintech Micro, Small, and Medium Enterprises (MSMEs) and proposes a scalable compliance framework tailored to their unique needs. As IoT adoption grows in the Fintech sector, these organizations face significant vulnerabilities that threaten their financial stability and operational efficiency, while also navigating complex regulatory environments. A quantitative study was conducted, collecting data from diverse Fintech professionals across various organizational sizes and sectors. Statistical analyses, including regression and variance tests, identified critical IoT vulnerabilities such as insecure firmware and weak authentication protocols as major risks. The frequency of IoT security incidents was found to have a significant impact on financial losses and operational disruptions. The study also examined the role of security metrics, revealing that proactive measures like risk assessments, real-time monitoring, and automated compliance reporting are strongly associated with improved regulatory adherence and reduced security breaches. The proposed IoT security compliance framework emphasizes modularity and scalability to accommodate the varying resources and complexities of Fintech MSMEs. Incorporating emerging technologies such as blockchain and fog computing, the framework provides an affordable and adaptable solution to enhance security posture and maintain compliance with standards like GDPR and PCI DSS. Despite challenges related to financial constraints and technical expertise, implementation of the framework resulted in measurable improvements in compliance levels, reduction in audit penalties, and increased stakeholder trust. Findings highlight the importance of structured, data-driven security practices and the need for external support mechanisms to help resource-limited organizations adopt effective IoT security measures. The research concludes that a scalable, standardized framework is essential for Fintech MSMEs to mitigate IoT-related risks while enabling growth and innovation within a rapidly evolving digital ecosystem. Future work is recommended to explore advanced AI-based threat detection, develop standardized IoT security metrics, and assess the practical implementation of decentralized security solutions for small and medium enterprises.